2007
DOI: 10.2337/dc06-2554
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Diabetic Nephropathy in an Urban South Indian Population

Abstract: OBJECTIVE -The aim of this study was to determine the prevalence of diabetic nephropathy among urban Asian-Indian type 2 diabetic subjects.RESEARCH DESIGN AND METHODS -Type 2 diabetic subjects (n ϭ 1,716), inclusive of known diabetic subjects (KD subjects) (1,363 of 1,529; response rate 89.1%) and randomly selected newly diagnosed diabetic subjects (NDD subjects) (n ϭ 353) were selected from the Chennai Urban Rural Epidemiology Study (CURES). Microalbuminuria was estimated by immunoturbidometric assay and diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
147
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(176 citation statements)
references
References 24 publications
22
147
6
1
Order By: Relevance
“…5 Population data on micro and macro vascular complications of diabetes are available in urban India. [6][7][8][9][10] However, such data were not available in rural India. This is largely because in rural areas, diabetes remains a neglected field, as awareness levels and accessibility to diabetes health care remains woefully inadequate.…”
Section: Symposiummentioning
confidence: 99%
“…5 Population data on micro and macro vascular complications of diabetes are available in urban India. [6][7][8][9][10] However, such data were not available in rural India. This is largely because in rural areas, diabetes remains a neglected field, as awareness levels and accessibility to diabetes health care remains woefully inadequate.…”
Section: Symposiummentioning
confidence: 99%
“…In a recent study from India, the risk factors determining the diabetic nephropathy in urban Asians are the duration of diabetes, the diabetic control and systolic blood pressure [12]. The consensus is that hyperglycemia by its action through glucotoxicity and lipotoxicity, hypertension and proteinuria contributes to nephrotoxicity in diabetics.…”
mentioning
confidence: 99%
“…As the disease progresses microalbuminuria ultimately leads to the development of macroalbuminuria and then progresses to loss of glomerular filtration rate and almost 95 % with diabetic nephropathy will develop diabetic retinopathy. 12 However such processes are more complicated in case of patients with type 2 diabetes, as these patients are also vulnerable to parenchymal kidney diseases other than classical diabetic glomerulosclerosis, that may include hypertensive disorders, atherosclerosis and lipid toxicity. Despite many research studies have suggested the key role of microalbuminuria in prediction of adverse clinical events which may includ all-cause mortality, cardiovascular endpoints and renal failure in non -diabetic patients, very few studies have been done investigating the potential association of microalbuminuria with that of retinopathy in patients having type 2 diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%